2012
DOI: 10.4149/bll_2012_003
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin converting enzyme gene (I/D) polymorphism with hypertension and type 2 diabetes

Abstract: Objectives: This study was conducted to determine the association of insertion/deletion (I/D) polymorphism of the ACE gene in hypertensive and T2DM subjects in Egyptian population. Background: The deletion (D) allele of the angiotensin-converting enzyme (ACE) gene has been studied in relation to hypertension and type 2 diabetes mellitus (T2DM) with contradictory results which might be due to ethnic and geographical variations. Methods: A total of 85 subjects participated in this study; hypertension (Group 1); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 21 publications
(22 reference statements)
7
37
0
2
Order By: Relevance
“…Many studies showed that polymorphisms of certain genes related to metabolism, including that of ACE, are also associated with the onset and development of Type 2-Diabetes [22, 24 -25]. There is a 287 bp DNA fragment insertion (I) and /or deletion(D) polymorphism in the intron 16 of ACE gene [22,26], which was recently studied [27][28][29][30][31] …”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that polymorphisms of certain genes related to metabolism, including that of ACE, are also associated with the onset and development of Type 2-Diabetes [22, 24 -25]. There is a 287 bp DNA fragment insertion (I) and /or deletion(D) polymorphism in the intron 16 of ACE gene [22,26], which was recently studied [27][28][29][30][31] …”
Section: Introductionmentioning
confidence: 99%
“…Doprinos istraživanju genetike metaboličkog sindroma u shizofreniji proizlazi i iz dviju studija nedavno provedenih u hrvatskoj populaciji koje su ispitale povezanost funkcijskog insercijsko-delecijskog polimorfizma (I/D) gena za angiotenzinkonvertirajući enzim (ACE) i funkcijske polimorfne varijante L162V u genu za PPARα s vrijednostima BMI-ja, te s koncentracijama glukoze i lipida u plazmi, u dvjestotinjak pacijenata sa shizofrenijom i shizoafektivnim poremećajem 153,154 . Spomenute polimorfne varijante prethodno su istražene povezano s metaboličkim sindromom ili njegovim komponentama u velikom broju studija u općoj populaciji, međutim, ne i u pacijenata sa shizofrenijom [155][156][157][158][159][160] . Značajno više vrijednosti glukoze u plazmi pronađene su u pacijentica heterozigota za ACE genotip (ID) u odnosu na pacijentice ACE-DD i ACE-II homozigote, dok su muškarci koji su u svojem ACE genotipu posjedovali D alel (ACE-DD homozigoti i ACE-ID heterozigoti) pokazali zanimljiv trend prema većim vrijednostima triglicerida 154 .…”
Section: Genetika Metaboličkog Sindroma U Shizofrenijiunclassified
“…However, the results obtained according to different areas of studies are still contradictory. In Japan (Higaki et al, 2000) and India (Zarouk et al, 2012), DD genotype significantly increased risk of developing EH. Whereas no effect of the presence of DD genotype was observed in Dutch (Schidmt et al, 1993), Tunisian (Kabadou et al, 2013), and Indonesian (Rasyid et al, 2012) populations.…”
Section: Introductionmentioning
confidence: 97%